Occupational Interests towards social services according to some variable (Field study in a sample of Tishreen University students) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The current research aimed to study differences in Attitudes between individuals belonging to the social pattern. It studied the variable of the college to which the students of the three faculties of social pattern as one of the patterns of professional orientation, which are the faculties of education, literature and nursing from the Tishreen University colleges.The Strong Scale for Professional Trends he (social service axis) was used as a research tool and was applied to a sample of 300 students.The results showed that there are differences on the scale of social services among the students of the Faculty of Education and Nursing for the benefit of students of Education. The results also revealed differences on the scale of social services among the students of the Faculty of Education and literature for the benefit of students of Education. And the absence of statistically significant differences on the scale between students of literature and Nursing.